2008
DOI: 10.1590/s0074-02762008000700003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polymorphisms in the mannose-binding lectin gene promoter among human immunodeficiency virus 1 infected subjects

Abstract: The present study investigated the prevalence of mutations in the -550 (H/L) and -221 (X/Y) mannose-binding lectin (MBL) gene promoter regions and their impact on infection by human immunodeficiency virus 1 (HIV-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
13
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
5
13
1
1
Order By: Relevance
“…Plasma MBL concentration was not a predictor of HIV status, CD4 + T cell count, and viral load. Plasma MBL deficiency and MBL2 genetic variants had no role in HIV disease progression in our study population defined as decrease in CD4 + T cell count and increase in viral load, in accord with other findings (Catano et al, 2008;Nielsen et al, 1995;Senaldi et al, 1995) but in contrast to other reports of a significant association Hundt et al, 2000;Tan et al, 2009;Vallinoto et al, 2008). The studies that showed similar results to ours were done in the USA among those with European origins and African Americans (Catano et al, 2008), UK (Senaldi et al, 1995), and Denmark (Nielsen et al, 1995).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Plasma MBL concentration was not a predictor of HIV status, CD4 + T cell count, and viral load. Plasma MBL deficiency and MBL2 genetic variants had no role in HIV disease progression in our study population defined as decrease in CD4 + T cell count and increase in viral load, in accord with other findings (Catano et al, 2008;Nielsen et al, 1995;Senaldi et al, 1995) but in contrast to other reports of a significant association Hundt et al, 2000;Tan et al, 2009;Vallinoto et al, 2008). The studies that showed similar results to ours were done in the USA among those with European origins and African Americans (Catano et al, 2008), UK (Senaldi et al, 1995), and Denmark (Nielsen et al, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…The studies that showed similar results to ours were done in the USA among those with European origins and African Americans (Catano et al, 2008), UK (Senaldi et al, 1995), and Denmark (Nielsen et al, 1995). Studies that showed contrasting results to ours were done in Denmark , China (Tan et al, 2009), Germany (Hundt et al, 2000), and Brazil (Vallinoto et al, 2008). The possible reasons why our results are different to others who found an association between MBL deficiency and disease progression might be due to differences in characteristics of the different populations studied or might be due to differences in sample sizes used.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The prevalence of mutations in the -550 (H/L) and -221 (X/Y) MBL gene promoter regions and their impact on HIV-1 infection were investigated in a population of 128 HIV-1 seropositive and 97 seronegative individuals, and there were no differences in the allele and haplotype frequencies between seropositive and seronegative status 9 . CD4 + T-lymphocyte counts were lower in the seropositive individuals carrying haplotypes LY, LX, and HX, as compared to those carrying the HY haplotype.…”
mentioning
confidence: 99%